EFFECT OF NITROGEN-FIXING BACTERIA ON GRAIN YIELD AND DEVELOPMENT OF FLOODED IRRIGATED RICE - Beutler, Amauri Nelson (2016)
This study aimed at evaluating the effect of Azospirillum brasilense, a nitrogen-fixing bacterium, on flooded irrigated rice yield. Evaluations were carried out in a shaded nursery, with seedlings grown on an Alfisol. Were performed two sets of experiments. In the first, were carried out four experiments using the flooded rice cultivars INIA Olimar, Puitá Inta-CL, Br Irga 409 and Irga 424; these trials were set up as completely randomized design in a 5x4 factorial scheme, with four replications. Treatments consisted of five nitrogen rates (0, 40, 80, 120 and 160 kg ha-1) and four levels of liquid inoculant Ab-V5 and Ab-V6 - A. brasilense (0, 1, 2 and 4 times the manufacturer's recommendation) without seed treatment. In second set, were performed two experiments using the cultivars Puitá Inta-CL and Br Irga 409, arranged in the same design, but using a 4x2 factorial. In this set, treatments were composed of four levels of Ab-V5 and Ab-V6 - A. brasilense liquid inoculant (0, 1, 2 and 4 times the recommendation of 100 mL ha-1), using rice seeds with and without insecticide and fungicide treatment. Shoot dry matter, number of panicles, and rice grain yield per pot were the assessed variables. The results showed that rice seed inoculation with A. brasilense had no effects on rice grain yield of the cultivars INIA Olimar, Puitá Inta-CL, Br Irga 409 and Irga 424.